Receptor-ligand interactions for optimized endocytosis in targeted therapies - Sung, Yejin; Choi, Youngjin; Kim, Eun Sun; Ryu, Ju Hee; Kwon, Ick Chan (Elsevier BV, 2025)
Receptor-mediated endocytosis plays a crucial role in the success of numerous therapies and remains central to advancing drug development. This process begins with ligand binding to specific receptors, triggering the internalization and intracellular trafficking of receptor-ligand complexes. These complexes are subsequently directed into distinct routes, either toward lysosomal degradation or recycling to the cell surface, with implications for therapeutic outcomes. This review examines receptor-ligand interactions as key modulators of endocytosis, emphasizing their role in shaping therapeutic design and efficacy. Advances in selecting receptorligand pairs and engineering ligands with optimized properties have enabled precise control over internalization, endosomal sorting, and trafficking, providing tailored solutions for diverse therapeutic applications. Leveraging these insights, strategies such as RNA-based therapies, antibody-drug conjugates (ADCs), and targeted protein degradation (TPD) platforms have been refined to selectively avoid or promote lysosomal degradation, thereby enhancing therapeutic efficacy. By bridging fundamental mechanisms of receptor-mediated endocytosis with innovative therapeutic approaches, this review offers a framework for advancing precision medicine.